Stapled versus hand-sewn cervical esophagogastric anastomosis in patients undergoing esophagectomy: A Retrospective Cohort Study - Mishra, Pramod Kumar (Ann Med Surg (Lond), 2016)
INTRODUCTION: Anastomotic leak is one of the main causes of morbidity following esophageal resection for carcinoma of the esophagus and gastroesophageal junction. We compared hand sewn and stapled cervical esophagogastric anastomotic techniques in terms of postoperative complications. METHODS: All patients who underwent esophagectomy with cervical esophagogastric anastomosis at a single academic center from 2004 to 2014 were included in the study. Both early and late complications were analyzed. RESULTS: 153 patients underwent resection for carcinoma of the esophagus and gastroesophageal junction. Of these 140 patients had esophagectomy with cervical esophagogastric anastomosis. 66 patients underwent a hand sewn anastomosis and 74 patients had a side-to-side stapled anastomosis fashioned. Both groups were comparable with respect to preoperative characteristics. There was no difference in the operative blood loss and T and N stage of the disease. The overall morbidity and mortality was 32.8% and 6.4%, respectively. Overall leak rate was 17%. There was no difference in the leak rates among two groups (12 in the hand-sewn group & 12 in the Stapled stapled group; p = 0.82). The rate of anastomotic stricture was significantly higher for the hand sewn group (16.1% vs 4.3%; p = 0.03) at median follow up of 30 months. CONCLUSION: Both hand sewn and stapled anastomotic techniques are equally effective way of performing a cervical esophagogastric anastomosis. However, patients having anastomotic leak develop anastomotic stricture more often in those having hand-sewn anastomosis compared to stapled anastomosis.